Effects of substitute allowance on match activity characteristics in Japanese professional football across 2019, 2020, and 2021 seasons - Ayabe, M.; Sunami, S.; Kumahara, H.; Ishizaki, S. (Journal of Sports Sciences, 2022)
This study aimed to examine the effects of substitute player allowance per match on running performance in Japanese professional football over three consecutive seasons with different numbers of maximum substitutes. Match running performance was obtained from all outfield players in the official matches of the 1st Division of the Japan Professional Football League over three seasons (2019/2020/2021; 22291 player files) by a 4th generation TRACAB® system which provided the total distance covered (TD) and the number of sprinting runs (SP; =24.0 km/h for=1.0 s). The players were divided according to play time: full match (STA), replaced during match (REP), and substitutes during match (SUB). The number of SUBs increased significantly from 2019 to 2021 (p < 0.05). SUB had a significantly higher average speed than STA and REP. The analysis of covariance with the number of recovery days, ambient temperature, and relative humidity as covariates revealed that the TD and SP significantly differed based on the number of SUBs (p < 0.05). Stepwise regression analysis showed that the number of SUBs significantly contributed to the TD and SP. These results suggest that the new law, which increased the maximum SUB allowance from three to five, improved the match running performance in Japanese professional football.